INDIVIDUAL FEATURES OF PATIENTS WITH PARANOID FORM OF SCHIZOPHRENIA, COMBINED WITH CANNABINOIDS USE - Кидонь, П.В. (World of Medicine and Biology, 2015)
The article presents the results of a study of the personality of patients with paranoid schizophrenia, combined with the cannabinoids use . Accentuated personality have been identified using the Leonhard-Shmishek technique. It have been revealed that the personality of patients with paranoid form of schizophrenia who use cannabinoids, has its own characteristics that distinguish it from paranoid schizophrenia patients without concomitant substance use, and mentally healthy individuals who use cannabinoids. The obtained data can be used in the treatment, rehabilitation and preventive measures in this group of patients.
Keywords: paranoid schizophrenia; cannabinoids; personality; Leonhard-Shmishek technique